Etude De La Variabilite Structurale Et Floristique Des Forets Sur Terre Ferme En Chefferie De Bahema-Boga (Province De L’ituri, RDC) - Nsangua, Benoit Mposo; Nseya, Hippollyte Nshimba; B., Faustin Boyemba; L., Roger Katusi; M., Faustin Mbayo; M., Laurianne Mbuyu (European Scientific Journal, ESJ, 2018)
The knowledge of the structural and floristic variability of forest is the principal tool which makes it possible to know the floristic composition of forest in an area. This paper focuses on analyzing the structural and floristic variability between compounds of forest on firm earth in chieftainship Bahema-boga in Ituri Province in Democratic Republic of Congo (DRC). The study provides knowledge and education to those responsible for environmental protection and those who are concerned with the forest based on the floristic potential for the conservation and the sustainable management of the forests. The structure and the floristic composition vary from one forest to another. The quantity of carbon stoke also vary due to the function of structures and floristic composition of forests. The forests play an important role in the reduction of CO2. The inventories of trees whose diameter is ≥ 10 cm have allowed us to collect the data to analyze this structural and floristic variability in a sample of 3 ha (plots) of forests in firm earth. The results obtained indicate that 812 inventoried individuals (trees) are extended in 16 species, 11 kinds, and 8 famillies. The total earth surface of inventoried individuals is 32,06 m2 /ha. The species of Cynometra sessiliflora dominated those forests with 408 individuals (50,25%). The diametric class of the most elevated inventoried plants are located between 10-20cm (63,17%). The family of the Fabaceae is better represented in those forests (73,65%).